Bacterial adhesion chemistry, biology and physics - Linke, Dirk.; Goldman, Adrian; SpringerLink (Online service). (Dordrecht Springer Netherlands, 2011)
Adhesion plays a major role in the bacterial lifestyle. Bacteria can adhere to organic and inorganic surfaces, to each other, and of course to host cells during pathogenesis. The focus of this book is: how are such adhesion phenomena best studied? Microbial genetics experiments have greatly enhanced our knowledge of what bacterial factors are involved in adhesion. For numerous reasons, though, biochemical and structural biology knowledge of the molecular interactions involved in adhesion are limited. One major problem has been a lack of interdisciplinary research and understanding in the field. On the one hand, the microbiologists lack detailed knowledge of the biophysical possibilities and have limited access to the frequently expensive instrumentation involved while on the other hand, the experts in these methods frequently do not have access to the biological materials, nor do they necessarily understand the biological questions to be answered. The purpose of this book is thus to overcome this gap in communication between researchers in biology, chemistry and physics and to display the many ways and means to investigate bacterial adhesion. We hope to stimulate new and ground-breaking research.
Adhesins of human pathogens from the genus Yersinia / J.C. Leo and M. Skurnik -- Adhesive mechanisms of Salmonella enterica / C. Wagner and M. Hensel -- Adhesion mechanisms of Borrelia burgdorferi / S. Antonara, L. Ristow and J. Coburn -- Adhesins of Bartonella spp. / F. O?Rourke ... [et al.] -- Adhesion mechanisms of plant-pathogenic Xanthomonadaceae / N. Mhedbi-Hajri, M.A. Jacques and R. Koebnik -- Adhesion by pathogenic Corynebacteria / E.A. Rogers, A. Das and H. Ton-That -- Adhesion mechanisms of Staphylococci / C. Heilmann -- Protein folding in bacterial adhesion: secretion and folding of classical monomeric autotransporters / P. van Ulsen -- Structure and biology of trimeric autotransporter adhesins / A. Lyskowski, J.C. Leo and A. Goldman -- Crystallography and electron microscopy of chaperone/usher pilus systems / S. Geibel and G. Waksman -- Crystallography of gram-positive bacterial adhesins / V. Krishnan and S.V. Narayana -- The nonideal coiled coil of M protein and its multifarious functions in pathogenesis / P. Ghosh -- Bacterial extracellular polysaccharides / K. Bazaka ... [et al.] -- Carbohydrate mediated bacterial adhesion / R.J. Pieters -- The application of NMR techniques to bacterial adhesins / F. Shewmaker -- Electron microscopy techniques to study bacterial adhesion / I. Grin, H. Schwarz and D. Linke -- EM reconstruction of adhesins: future prospects / F. Ilaria and F. Giusti -- Atomic force microscopy to study intermolecular forces and bonds associated with bacteria / S.K. Lower -- Assessing bacterial adhesion on an individual adhesin and single pili level using optical tweezers / O. Axner ... [et al.] -- Short time-scale bacterial adhesion dynamics / J. Geng and N. Henry -- Deciphering biofilm structure and reactivity by multiscale time-resolved fluorescence analysis / A. Bridier ... [et al.] -- Inhibition of bacterial adhesion on medical devices / L.R. Rodrigues.
Electronic reproduction.
Keywords: Bacteria -- Adhesion; Bacterial adhesion; Electronic books